Parenting styles and coping strategies in PKU early detected children - Pardo Campos, Maria Laura (2021)
Phenylketonuria (PKU) requires tight control to prevent neurocognitive impairment but reports show that patients may present mild cognitive defects related to higher impulsivity. We hypothesize that chronic intervention may influence the parents and child bonding and the child´s resources to face problems. To describe the PKU parenting styles perceived by the children (PS) and their coping strategies (CS) assessing their relationship with impulsivity, 30 early diagnosed and adequately treated PKU children and 30 non PKU aged-paired controls (CG) were compared. The Argentine Children´s Coping Questionnaire, Argentine Scale Perception of the Relationship with Parents, WISC IV Comprehension Subtest, and CPT II test were administered. PKU PS were based on control: strict to pathologic in the mother and acceptable in the father (both p<0.05 vs. CG). Children significantly sought greater support and showed less emotional control when facing conflicts. These characteristics positively correlated with maternal control r:.383 and r:.398 (both p<0.05). Impulsivity was higher in PKU (p<0.05) but didn´t associate with PS or CS. Maternal strict control wasn´t linked to the higher impulsivity found (possibly neurobiologically based). Nevertheless, if both factors are present, patients may develop a psychological and/or behavioral trait of greater dependency and impulsivity that must be considered in their follow-up.